2020
DOI: 10.3389/fpsyt.2020.626807
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 Suicide Survivors—A Hidden Grieving Population

Abstract: Present time has been dominated by the COVID-19 pandemic. People are grieving several non-death related situations: the loss of a job, of a status, of a role, of their life. Restrictive measures and uncertainty about the future makes individuals vulnerable to feelings of hopelessness and helplessness. Mental health support has been hindered and teams are reinventing themselves to reach people in need. Nevertheless, decompensation of previous psychiatric disorders, increasing levels of depression and anxiety, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 106 publications
0
12
0
7
Order By: Relevance
“…One possible interpretation for the absence of significant improvement of the GHQ-28 and STAI scores in male subjects might be due to the lack of communication in male patients, which could have contributed to greater anxiety. Although the quantity of information on the virus and disease increased at T2, it has been suggested that COVID-19-related mental health problems such as suicides ( 22 ) and the complex grief of bereaved families may increase ( 23 ). The course of the pandemic is still unpredictable.…”
Section: Discussionmentioning
confidence: 99%
“…One possible interpretation for the absence of significant improvement of the GHQ-28 and STAI scores in male subjects might be due to the lack of communication in male patients, which could have contributed to greater anxiety. Although the quantity of information on the virus and disease increased at T2, it has been suggested that COVID-19-related mental health problems such as suicides ( 22 ) and the complex grief of bereaved families may increase ( 23 ). The course of the pandemic is still unpredictable.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, cases of individuals who died through suicide have been reported, mainly in the media, linking their deaths to the fear of COVID-19 infection, fear of transmitting SARS-CoV-2 to others, anxiety over COVID-19, fear of isolation due to imposed country pandemic-related lockdown and a lack of knowledge. Further triggers that have been identified for suicides related to the COVID-19 pandemic are xenophobia, COVID-19-related stigma and social boycott, financial insecurities and uncertainty concerning the future ( 73 , 74 ). In previous a review article on suicide reports, possible factors and predictors of COVID-19-related suicide were categorized according to ‘social isolation and distancing’, ‘worldwide lockdown creating economic recession’, ‘stress, anxiety and pressure in medical healthcare professionals’ and ‘social boycott and discrimination’ ( 73 ).…”
Section: Suicidal Behaviors In the Context Of The Covid-19 Pandemicmentioning
confidence: 99%
“…Moreover, it is worth noting, that each suicide may affect 5-80 individuals, including nuclear family members, relatives, friends and acquaintances, which are known as ‘suicide survivors’. Suicide survivors face an increased risk of prolonged or persistent complex bereavement (with rates reaching up to 40%), depression, anxiety and substance-abuse disorders, as well as suicidal behaviors, while social stigma and feelings of shame may discourage them from seeking mental health-related assistance ( 74 , 86 ). The suicide of a ‘significant other’ amidst the COVID-19 pandemic is even more challenging for suicide survivors, who are already struggling to adjust to new conditions and are likely experiencing psychological difficulties.…”
Section: Suicidal Behaviors In the Context Of The Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…The high degree of exposure to the disease COVID-19 and the social and economic effects associated with the pandemic may result in some experiencing a worsening of these psychiatric characteristics (particularly anxiety, depression, and stress), with possible adverse effects on suicidal behaviors [16,17]. The death of close family members and friends, the stigma towards infected people and their families, isolation, physical distancing, changes caused by the digitalization of educational and work activities, unemployment and economic insecurity, information overload, or fear about the lack of social health resources are all critical risk factors that have contributed to the increase in ideation and suicide during the pandemic [18].…”
Section: Introductionmentioning
confidence: 99%